The gap between expectations and reality: A qualitative study of psychosocial challenges of young childhood cancer survivors from the PACCS study. (27th August 2022) - Larsen, Marie Hamilton; Hansson, Kjerstin Enger; Larsen, Elna Hamilton; Fridh, Martin Kaj; Petersen, Natasha Nybro; Mellblom, Anneli Victoria; Ruud, Ellen; Larsen, Hanne Baekgaard; Lie, Hanne Cathrine
Abstract: Objective: In this sub‐study from the 'PACCS' study, we explored the psychosocial experiences of children and adolescents in everyday life post‐cancer treatment and the possible factors that can moderate these experiences. Methods: This is a qualitative explorative study using semi‐structured interviews with 43 childhood cancer survivors between the ages of nine and 18 from Norway and Denmark. We conducted a secondary thematic analysis using Malterud's systematic text condensation. Results: Two main themes were identified: 'The post‐treatment gap between expectations and reality' comprised two subthemes: (1) lack of mastery and feeling different and (2) lack of understanding and acceptance. The second main theme, 'Managing the gap', comprised three subthemes: (1) information and knowledge, (2) adjustments and adaptions and (3) social support and openness. The findings reveal that the psychosocial challenges resulted from the remaining ability gap(s). Measures such as tailored information, school adjustments and social support were potential dynamic factors affecting the gap(s) positively or negatively. Psychosocial challenges post‐treatment are experiences of lack of acceptance and understanding from others. Conclusion: To safeguard a positive transition back to everyday life, health care providers should support the survivors' psychosocial care, including getting back to school and re‐entering social interactions.